Effects of a liver APOEε4‐genotype on synaptic integrity, gliosis and insulin signaling in the brain: Molecular and cell biology/synaptic disruption. (7th December 2020) - Giannisis, Andreas; Patra, Kalicharan; Edlund, Anna K.; Rosa, Andrés De La; Nieto, Lur Agirrezabala; Gras, Joan Benedicto; Moussaud, Simon; Bengtsson, Tore; Fu, Yuan; Bu, Guojun; Bial, Greg; Foquet, Lander; et al.
Abstract: Background: APOEε4 is the strongest genetic risk factor for AD[1]. Although plasma apoE does not cross the blood‐brain‐barrier[2], altered plasma apoE levels have been linked to increased risk of AD[3] and to unfavorable CSF Aβ42 and tau levels[4]. Translation of results from studies of apoE in rodents to the human situation is difficult due species‐specific difference for instance in lipid metabolism[5]. Here we have studied the effects of a humanized APOE ε4 liver[6] on synaptic integrity, insulin signaling and gliosis in a mouse model that reproduces the human plasma profile and that retains its endogenous apoE expression in the brain. Method: Tissue samples from the cortex, hippocampus, cerebellum and thalamus were obtained from FRGN mice with humanized APOE ε2/ε3 (n=4) versus APOE ε4/ε4 (n=8) livers, and from APOE ε3/ε3 (n=3) and APOE ε4/ε4 (n=3) TR mice. Using established protocols[7], nuclei‐ and synaptosome‐enriched, and synaptosome‐depleted fractions were generated and analyzed for contents of markers relating to synapse integrity, gliosis and insulin signaling using western blotting. Levels of apoE4 were assessed in plasma from FRGN mice with humanized APOE ε4/ε4 livers. Result: Cortical and hippocampal levels of endogenous apoE, cortical levels of tubulin‐βIII, AMPAR, NMDAR, bassoon, mTOR, pAkt and a‐synuclein as well as hippocampal levels of synaptophysin, EAAT2, GFAP, NMDAR, pmTORS2448 and pIRS616 were reduced in FRGN mice with humanized APOE ε4/ε4 versus APOE ε2/ε3 livers (p≤0.05). Several of these findings were recapitulated in brain tissues from APOE ε4/ε4 versus APOE ε3/ε3 TR mice (p≤0.05). In both mouse models we observed a shift of a‐synuclein content from the synaptosomal (reduction) to the extra‐synaptosomal (increase) compartment (p<0.05). Altered expression levels of synaptic markers were also found in the thalamus and to a lesser extent in the cerebellum. Plasma levels of apoE appeared lower in the humanized APOE ε4/ε4 liver mice and correlated positively to cortical levels of endogenous apoE but negatively to various markers of synaptic integrity and insulin signaling mainly in the hippocampus. Conclusion: We here provide the first evidence of a profound and negative effect of a liver APOEε4 phenotype in a human‐like setting, on key markers related to brain synaptic integrity, insulin signaling and glial cells involved in neuroinflammation.